Peran Nilai-nilai Islam dalam Membangun Multikulturalisme Perspektif Kontemporer - Munawaroh, Masulil (Journal of Education and Learning Innovation, 2025)
In the era of globalization, which brings about increased cultural, ethnic, and religious diversity, there is a growing urgency to explore religious approaches that support harmonious social coexistence. This study is motivated by the need to develop an Islamic-based multiculturalism as a response to the challenges of intolerance and exclusivism. The primary objective of this research is to examine how Islamic values such as tasāmuh (tolerance), ta‘āruf (mutual understanding), ‘adl (justice), and rahmah (compassion) can contribute to strengthening multiculturalism in contemporary society. This research employs a qualitative approach through critical literature review and contextual analysis of Islamic texts and the social practices of Muslims. The findings indicate that when interpreted in a moderate and contextual manner, Islamic values possess transformative potential in fostering an inclusive and peaceful social order. Moreover, the study highlights that exclusive interpretations of religious texts remain a significant challenge in promoting multicultural ideals. The implications of this research underscore the importance of Islamic education and preaching that prioritize moderation and intercultural dialogue as key strategies for enhancing social coexistence and contributing to a more just, tolerant, and humane global civilization.